Green synthesis of silver nanoparticles and their antibacterial effects - Xin, Xiaoqian; Qi, Chunli; Xu, Liang; Gao, Qin; Liu, Xiaowen (Frontiers in Chemical Engineering, 2022)
Antibacterial resistance is by far one of the greatest challenges to global health. Many pharmaceutical or material strategies have been explored to overcome this dilemma. Of these, silver nanoparticles (AgNPs) are known to have a non-specific antibacterial mechanism that renders it difficult to engender silver-resistant bacteria, enabling them to be more powerful antibacterial agents than conventional antibiotics. Hence, most of the effectiveness studies based on AgNPs so far have shown promising results in both Gram-positive and Gram-negative bacteria. The aim of this review is to cover the green synthesis of AgNPs as antibacterial agents, while other AgNPs-related insights (e.g., antibacterial mechanisms, potential toxicity, and medical applications) are also reviewed. Their additive value in the exploitation of alternative, more effective antibacterial agents against drug-resistant bacteria has been stressed.